2005
DOI: 10.1093/sleep/28.8.1007
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome and Attention-Deficit/Hyperactivity Disorder: a Review of the Literature

Abstract: Although still limited, evidence from clinical studies demonstrates an association between RLS and ADHD or ADHD symptoms. Further clinical studies using standard criteria and procedures are needed to better estimate the degree of association. Epidemiologic studies are required to assess the relationship between ADHD and RLS symptoms in nonclinical samples. Further investigations should address the mechanisms underlying the relationship between RLS and ADHD. Several dopaminergic agents seem to be promising trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
216
2
25

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(254 citation statements)
references
References 0 publications
11
216
2
25
Order By: Relevance
“…Two of the four ADHD probands with PTPRD deletions reported symptoms consistent with restless legs syndrome (RLS), which shares high rates of bidirectional comorbidity as well as dopaminergic dysfunction with ADHD. 33,34 Intriguingly, a recent genome-wide association study has implicated PTPRD as a locus for RLS. 35 Moreover, genetic variants of PTPRD associate with bronchial asthma, 36 which is reported to occur at higher rates in children with ADHD, 37 and RLS patients have been shown to have increased use of asthma medications.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the four ADHD probands with PTPRD deletions reported symptoms consistent with restless legs syndrome (RLS), which shares high rates of bidirectional comorbidity as well as dopaminergic dysfunction with ADHD. 33,34 Intriguingly, a recent genome-wide association study has implicated PTPRD as a locus for RLS. 35 Moreover, genetic variants of PTPRD associate with bronchial asthma, 36 which is reported to occur at higher rates in children with ADHD, 37 and RLS patients have been shown to have increased use of asthma medications.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, previous studies have shown that all of these conditions might co-occur frequently (Cortese et al 2005). In this study, our aim was to investigate the relationship among iron stores (indicated by serum ferritin), iron deficiency and RLS in children and adolescents with ADHD.…”
mentioning
confidence: 98%
“…Most studies of RLS focus on the adult population, although about 38 % of adults with RLS in one series reported a history of symptom onset before the age of 20 years of age [95], and recent prevalence estimates of pediatric RLS in the general population are about 1.9-2 % of children and adolescents in the U.S. and U.K., with 25-50 % reporting moderate to severe symptoms [96]. Low ferritin levels, a positive family history in the majority [96], and/or ADHD [97,98] or other mood disturbances have been identified as associations at diagnosis [99,100]. Furthermore, despite the conventional differentiation between RLS and periodic limb movement (PLM) disorder, PLMs are common in pediatric RLS and the presence of PLMs is incorporated into the consensus criteria.…”
Section: Restless Legs Syndrome (Rls)mentioning
confidence: 95%